A nucleosome-dependent static loop potentiates estrogen-regulated transcription from the Xenopus vitellogenin B1 promoter in vitro. - Schild, C (1993)
We describe the transcriptional potentiation in estrogen responsive transcription extracts of the Xenopus vitellogenin B1 gene promoter through the formation of a positioned nucleosome. Nuclease digestion and hydroxyl radical cleavage indicate that strong, DNA sequence-directed positioning of a nucleosome occurs between -300 and -140 relative to the start site of transcription. Deletion of this DNA sequence abolishes the potentiation of transcription due to nucleosome assembly. The wrapping of DNA around the histone core of the nucleosome positioned between -300 and -140 creates a static loop in which distal estrogen receptor binding sites are brought close to proximal promoter elements. This might facilitate interactions between the trans-acting factors themselves and/or RNA polymerase. Such a nucleosome provides an example of how chromatin structure might have a positive effect on the transcription process.